The Mechanisms of Ferroptosis and the Applications in Tumor Treatment: Enemies or Friends? - Tan, Shuzheng; Kong, Ying; Xian, Yongtong; Gao, Pengbo; Xu, Yue; Wei, Chuzhong; Lin, Peixu; Ye, Weilong; Li, Zesong; Zhu, Xiao (Frontiers in Molecular Biosciences, 2022)
Ferroptosis, as a newly discovered non-apoptotic cell death mode, is beginning to be explored in different cancer. The particularity of ferroptosis lies in the accumulation of iron dependence and lipid peroxides, and it is different from the classical cell death modes such as apoptosis and necrosis in terms of action mode, biochemical characteristics, and genetics. The mechanism of ferroptosis can be divided into many different pathways, so it is particularly important to identify the key sites of ferroptosis in the disease. In this review, based on ferroptosis, we analyze the main pathways in detail. More importantly, ferroptosis is linked to the development of different systems of the tumor, providing personalized plans for the examination, treatment, and prognosis of cancer patients. Although some mechanisms and side effects of ferroptosis still need to be studied, it is still a promising method for cancer treatment.